Функціональні особливості вживання модальних дієслів в англомовних юридичних текстах: параметри частоти та сполучуваності - Карамишева, Ірина (Видавництво Львівської політехніки, 2017)
The presented research focuses on the functional peculiarities of modal verbs as means of modality expression in legal discourse with the aim to define the frequency of their usage in distribution agreements. The material selected for the research consists of 100 English contracts as corpora for the analysis. All the analyzed documents have been taken from the Internet sourses. The average length of each of the analyzed texts is about 17,000 words in one text. On the basis of the material presented in the theoretical English grammars, basic modal verbs were selected and became the object of study. The examples of modal verbs usage in the distribution agreements were analyzed, which allowed describing their basic functional characteristics as well as combinability patterns. It was found that the value of modal verbs is created by context and grammatical structures in which they are used. The frequency of occurrence of specific modal verbs in legal texts is different from their usage in common everyday language. The analysis leads to the conclusion that there is a need to conduct further studies that will determine exact translations of each modal verb and themorphological and syntactic forms they take.
Keywords: модальність; модальні дієслова; функціональні характеристики; частота вживання; юридичний дискурс; договір дистрибуції